Pendidikan EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN DI ERA DIGITAL DI SEKOLAH SMK N 1 PERCUT SEI TUAN - Salsabila Erliani; Nadia Sabrina Siregar; Abdul Fattah Nasution (Cemara Education and Science, 2024)
The use of learning media in the digital era opens wide doors for global education access. With technology, learning can be tailored to individual learning styles, increasing engagement and providing a wider variety of resources. This creates a learning environment that is dynamic and responsive to student development. This article aims to broaden the insight of prospective educators so they can choose which learning media are effective to use in this digital era. The research method used by the researchers is a descriptive qualitative method by conducting interviews and document studies. Effective learning media is a means of exchanging information between educators and students so that students can absorb lessons that are communicated clearly and concisely, thereby improving learning outcomes. Choosing the right media is one of the key factors for success in planning and implementing lessons. Effective use of learning media can increase student interaction during the learning process. Apart from that, students are happy with this educational media because it can maximize the quality of their learning outcomes